THE VIRTUOUS CHARACTER IN THE NOVEL "THE ROSE" BY HOSSAM KHAWAM AL YAHYA - Assist. Prof. Hadeel Nashat Aswad Hanaf (Journals Park Publishing, 2024)
This study seeks to shed light on the concept of the virtuous character in the novel (The Rose) at two levels: the mono-typical, and the complex, transformative, by presenting the course of events specific to the character, of which the character is the primary focus in moving it, which requires examining the path of this character’s transformations or fluctuations between goodness and goodness. And evil or virtue and vice. As well as revealing its patterns and levels of presence in terms of simplicity or typicality, complexity or composition, in a way that reveals its references and social, humanitarian and moral backgrounds, in a poor, backward society - as depicted in the novel - which is the village of (Imam Askar) located on the western bank of the Rose River. The novel follows the approach of modern novels in its adoption of multiple voices, or collective heroism, in terms of depicting the social agency influencing the course of events, away from the stereotypical image of depicting the single heroic character, which placed all the work’s characters on the same level in terms of influence and effectiveness. The research problem is that the novel simultaneously combines elements of the modern novel, such as polyphony and a focus on multiple characters, with aspects of the traditional novel, particularly in its plot structure and character development within the narrative framework.